PENGARUH PENAMBAHAN TEPUNG DAUN INDIGOFERA ZOLLINGERIANA DALAM RANSUM TERHADAP PRODUKSI DAN BERAT TELUR AYAM ARAB - Muhammad Amrullah Pagala; Ali Bain; Asis Surajat (Universitas Halu Oleo, 2018)
This study aimed to evaluate the effect of using leaf flour of Indigofera zollingeriana which was added to the ration on the productivity and quality of Arab chicken eggs. This research conducted in March to May of 2018. This research conducted at the Permata Poultry Farm Group in Wua Wua Village, Kendari. This research used a completely randomized design with four (4) treatments and four (4) replications. The experimental ration which was tested consisted of: P0 = The Ration contained 0% Indigofera leaf flour, P1 = ration containied 10% Indigofera leaf flour, P2 = Ration contained 15% Indigofera leaf flour, and P3 = Ration contained 20% Indigofera leaf flour. The parameters were observed feed consumption, egg weight, feed conversion, daily egg production. The research data were analyzed by using Analysis of Variance (ANOVA) based on RAL in using Statistical Product and Service Solutions (SPSS) software. If the treatment has a significant effect, further testing will be carried out with the Duncan Multiple Range Test. The results of this study showed that the addition leaf flour of indigofera zollingeriana in Arab chicken rations affected the feed conversion and egg weight of Arabic chicken, however indigofera leaf flour did not affect the feed consumption and egg production of Arab chickenKeywords: Indigofera Zollingeriana, Feed conversion, Egg Production, Arabic Chicken.